REDUCING AFFECTIVE FACTORS IN SLA: KEY SOLUTIONS TO MAXIMIZE THE OUTCOME OF LEARNING ENGLISH - Olena Kasatkina-Kubyshkina (Pavlo Tychyna Uman State Pedagogical University, 2018)
The article deals with the factors having an effect on second language acqui-sition, namely affective factors; individual, cognitive and metacognitive factors; demographic variables and teacher-related factors. The author concentrates on the set of affective factors which have both positive and negative influence on SLA. The author investigates the theoretical basis for studying this problem by foreign scholars and analyses the influence of affective factors by exploring their psycho-logical background. The article covers the key scientific and methodological guide-lines on reducing the negative impact of affective factors by developing and impro-ving empathic skills and developing assertive behaviour in order to maximize the outcome of learning English. The author names and illustrates the principal concepts to develop both affec-tive and cognitive empathy amongst current lesson plans. It is suggested to create the environment, set an example, include lots of stories and use literature to teach different perspectives, work on communication strategies, offer collaborative group tasks, be metacognitive about students' state of empathy. On equal terms with empathy assertiveness, a direct, strong and calm style of communication which focuses on achieving a healthy compromise that respects everyone involved is emphasized to demand advanced development. To maximize the outcome of learning it is up to a teacher to implement «I» statements, escalation, verbs change, verbal and non-verbal language control into the classroom.